A literature review on sexual violence by authority figures and its psychological impact on women and children - Wulandari, Desy; Simangunsong, Jojor Vivi; Husna, Rifqohhul; Sugiarti, Lucia Rini; Suhariadi, Fendy (Universitas Ahmad Dahlan, 2025)
Sexual violence perpetrated by authority figures such as teachers, lecturers, religious leaders, medical professionals, and law enforcement officers constitutes a severe violation of human rights with profound psychological consequences, particularly for women and children. This study employs a Systematic Literature Review (SLR) methodology to analyze 11 national and international journal articles published between 2020 and 2024. The aim of this review is to explore the dynamics of power relations, the psychological impact on survivors, barriers to recovery, and intervention strategies. Findings reveal that unequal power relations between perpetrators and victims significantly contribute to the occurrence of sexual violence and hinder the recovery process. Survivors frequently experience severe psychological symptoms, including post-traumatic stress disorder (PTSD), depression, dissociation, and developmental disturbances especially in children. Recovery barriers include societal stigma, limited legal support, and the normalization of the perpetrator's authority. Effective recovery strategies identified include Eye Movement Desensitization and Reprocessing (EMDR), Cognitive Behavioral Therapy (CBT), emotional support from family, and community-based approaches. This study highlights the urgent need for integrated, trauma-informed interventions and the strengthening of legal protection systems to break the cycle of sexual violence perpetrated by authority figures.